On a kinked crack model to describe the influence of material microstructure on fatigue crack growth - Andrea Spagnoli; Andrea Carpinteri; Sabrina Vantadori (Fracture and Structural Integrity)
Threshold condition and rate of fatigue crack growth in both short and long crack regime appear to be significantly affected by the degree of crack deflection. In the present paper, a theoretical model of a periodically-kinked crack is presented to describe the influence of the degree of crack deflection on the fatigue behavior. The kinking of the crack is due to a periodic self-balanced microstress field having a length scale, d. By correlating the parameter d with a characteristic material length (e.g. average grain size in metals, maximum aggregate dimension in concrete), the possibility of using the present model to describe some experimental findings related to crack size effects in fatigue of materials is explored. Well-known experimental results concerning two different situations (fatigue threshold and fatigue crack growth in the Paris regime) are briefly analysed.